Integrasi Kesejahteraan Emosional dalam Desain Organisasi : Pendekatan Humanistik terhadap Efektivitas Kerja - Putri Khoirina Nuzullah; Fiana Mahfujah; Abdurrohman Al Faiz; Hesti Kusumaningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the context of modern organizations that increasingly demand high productivity, employees’ emotional well-being is often overlooked in organizational design. This study aims to explore how a humanistic approach can be integrated into organizational design to create a work environment that is not only efficient but also supportive of emotional well-being. Using a literature review method complemented by interviews and observations of workplace dynamics, this study finds that organizations still tend to adopt bureaucratic and technocratic approaches that neglect employees’ psychological dimensions. As a result, issues such as burnout, decreased motivation, and low work engagement emerge. The findings highlight the need for a paradigm shift in organizational design—from a purely structural system toward a humanistic design that considers emotional needs. This study emphasizes that emotional well-being must be positioned as a strategic element in organizational design, not merely as a supplementary effort. Thus, work effectiveness and emotional well-being can be sustainably aligned.